Identification of infusion strategy for achieving repeatable nanoparticle distribution and quantification of thermal dosage using micro-CT Hounsfield unit in magnetic nanoparticle hyperthermia. (17th February 2016) - LeBrun, Alexander; Joglekar, Tejashree; Bieberich, Charles; Ma, Ronghui; Zhu, Liang
Abstract: Objectives : The objective of this study was to identify an injection strategy leading to repeatable nanoparticle deposition patterns in tumours and to quantify volumetric heat generation rate distribution based on micro-CT Hounsfield unit (HU) in magnetic nanoparticle hyperthermia. Methods : In vivo animal experiments were performed on graft prostatic cancer (PC3) tumours in immunodeficient mice to investigate whether lowering ferrofluid infusion rate improves control of the distribution of magnetic nanoparticles in tumour tissue. Nanoparticle distribution volume obtained from micro-CT scan was used to evaluate spreading of the nanoparticles from the injection site in tumours. Heating experiments were performed to quantify relationships among micro-CT HU values, local nanoparticle concentrations in the tumours, and the ferrofluid-induced volumetric heat generation rate ( qMNH ) when nanoparticles were subject to an alternating magnetic field. Results : An infusion rate of 3 µL/min was identified to result in the most repeatable nanoparticle distribution in PC3 tumours. Linear relationships have been obtained to first convert micro-CT greyscale values to HU values, then to local nanoparticle concentrations, and finally to nanoparticle-induced qMNH values. The total energy deposition rate in tumours was calculated and the observed similarity in total energy deposition rates in all three infusion rate groups suggests improvement in minimising nanoparticle leakage from the tumours. The results of this study demonstrate that micro-CT generated qMNH distribution and tumour physical models improve predicting capability of heat transfer simulation for designing reliable treatment protocols using magnetic nanoparticle hyperthermia.